If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 + -8(x + -1) = 3x + 8 Reorder the terms: 2x + 9 + -8(-1 + x) = 3x + 8 2x + 9 + (-1 * -8 + x * -8) = 3x + 8 2x + 9 + (8 + -8x) = 3x + 8 Reorder the terms: 9 + 8 + 2x + -8x = 3x + 8 Combine like terms: 9 + 8 = 17 17 + 2x + -8x = 3x + 8 Combine like terms: 2x + -8x = -6x 17 + -6x = 3x + 8 Reorder the terms: 17 + -6x = 8 + 3x Solving 17 + -6x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 17 + -6x + -3x = 8 + 3x + -3x Combine like terms: -6x + -3x = -9x 17 + -9x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 17 + -9x = 8 + 0 17 + -9x = 8 Add '-17' to each side of the equation. 17 + -17 + -9x = 8 + -17 Combine like terms: 17 + -17 = 0 0 + -9x = 8 + -17 -9x = 8 + -17 Combine like terms: 8 + -17 = -9 -9x = -9 Divide each side by '-9'. x = 1 Simplifying x = 1
| 6(-8a+4)=-8(5a+1) | | 2a-8+5a=10+7a | | 89=-3(5k-3)-k | | -42m-11=67 | | 5(n-7)-(3-4n)=8n | | -2x^3=-128 | | 25-(-41)= | | x^2(x^2)-16(x^2-1)=0 | | -29-6x=-5(-5x+1)-7x | | Sinx=3 | | 2b+58b=35 | | -21+5+-9=3(t-4)-5 | | 71=6(4n-8)-7n | | 2(x-5)=3(x-1) | | s+6=78 | | 2x+3y-5x+5y= | | 5(1+6a)=-39+8a | | 2+2v=-2 | | 2z^3+9z^2=5z | | 5b-16-8n=-10 | | 7(y+1)=49 | | K=17 | | X+3=-32 | | 15-f=-23 | | 4-5(x+3)=25 | | -22+7r=6(r-4) | | 3x+7+6x+11=90 | | 4x+1=11x | | -2(5y+5)=4 | | 3*x=10 | | 8+16=-3(5x-8) | | 9(6x-5)=279 |